Percepatan Reformasi Birokrasi Melalui Penerapan e-Government oleh Pemerintah Kota Padang - Rusnita, Widya Cancer; Aromatica, Desna; Putera, Roni Ekha (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
In the last 20 years, various reform efforts have been carried out with different names, ranging from the concept of new public management to one of them, the concept of e-Government. The city of Padang applies the concept of e-Government through a smart city. However, based on the results of the 2022 smart city evaluation, Padang City is ranked lowest in West Sumatra, even though as a provincial capital it has great potential to develop e-Government. The purpose of writing this article is to analyze the extent of the e-Government reforms implemented by the Municipal Government of Padang. The research method uses descriptive qualitative. To analyze it, the researcher used the concepts put forward by Dwiyanto including Productivity, Service Quality, Responsiveness, Responsibility and Accountability. From the discussion it can be concluded that the implementation of e-Government has had a significant impact on accelerating bureaucratic reform. However, there are still deficiencies in the form of capacity and quality of human resources in each OPD which are still lacking and e-Government applications have not been integrated in one system.